Two different strength training and untrained period effects in children - Coskun, A.; Sahin, G. (Journal of Physical Education and Sport, 2014)
The purpose of this study was to investigate effects of different strength training in trained period and untrained period. Thirty children (1st group weight mean: 30.50 ± 7.04 kg; height mean: 128.65 ± 6.74 cm; BMI: 18.06 ± 2.80 83 kg/m2 and 2nd group weight mean: 28.78 ± 4.50 kg; height mean: 131.12 ± 2.80 cm; BMI: 17.11 ± 2.83 kg/m2) participated to this study. Strength training was applied for 6 weeks. The children were divided to two groups as elastic band group and body weight training group. Height and weight measurements, leg strength test, sit-up test and push-up test were used in the study. All the tests were applied five times. Paired t- test, one Way ANOVA and repeated ANOVA statistics tests were used to analyze the data. The study results show that there were significant differences in leg strength and repetition of push-up between trained with elastic bands group and body weight after training group (p<0.05). There was no significant difference between sit-up (p>0.05). The time-dependent significant differences were found in push-ups, leg strength and sit-up (p<0.05).